Multilingual User Modeling for Personalized Re-ranking of Multilingual Web Search Results - GHORAB, MOHAMMED RAMI; ZHOU, DONG; LAWLESS, SEAMUS; WADE, VINCENT PATRICK (My University, 2012)
This paper proposes a novel method to represent user models in a multilingual manner which caters for multilingual Web search users. Furthermore, an evaluation is presented which examines a result re-ranking algorithm that is based upon that model.
PUBLISHED
Keywords: User Modeling; Personalization; Multilingual Information Retrieval; Result Adaptation; Web Search